Human Echinococcosis Mortality in the United States, 1990–2007 - Bristow, Benjamin N. (Public Library of Science, 2012)
BACKGROUND: Despite the endemic nature of Echinococcus granulosus and Echinococcus multilocularis infection in regions of the United States (US), there is a lack of data on echinococcosis-related mortality. To measure echinococcosis-associated mortality in the US and assess possible racial/ethnic disparities, we reviewed national-death certificate data for an 18-year period. METHODOLOGY/PRINCIPAL FINDINGS: Echinococcosis-associated deaths from 1990 through 2007 were identified from multiple-cause-coded death records and were combined with US census data to calculate mortality rates. A total of 41 echinococcosis-associated deaths occurred over the 18-year study period. Mortality rates were highest in males, Native Americans, Asians/Pacific Islanders, Hispanics and persons 75 years of age and older. Almost a quarter of fatal echinococcosis-related cases occurred in residents of California. Foreign-born persons accounted for the majority of echinococcosis-related deaths; however, both of the fatalities in Native Americans and almost half of the deaths in whites were among US-born individuals. CONCLUSIONS/SIGNIFICANCE: Although uncommon, echinococcosis-related deaths occur in the US. Clinicians should be aware of the diagnosis, particularly in foreign-born patients from Echinococcus endemic areas, and should consider tropical infectious disease consultation early.